2013
DOI: 10.1093/ntr/ntt061
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Cigarettes Among State Tobacco Cessation Quitline Callers

Abstract: This study offers a preliminary look at e-cigarette use among state quitline callers and is perhaps the first to describe e-cigarette use in a large group of tobacco users seeking treatment. The notable rates of e-cigarette use and use of e-cigarettes as cessation aids, even though the U.S. Food and Drug Administration has not approved e-cigarettes for this purpose, should inform policy and treatment discussions on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
188
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(205 citation statements)
references
References 12 publications
14
188
2
1
Order By: Relevance
“…Previous research has shown that current smokers do indeed use e-cigarettes in situations where they cannot smoke cigarettes. [36][37][38] If permitted in smoke-free areas, e-cigarettes could be used to subvert smoking restrictions and re-normalize smoking. 6 Social denormalization of smoking played a critical role in reducing smoking prevalence and youth initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that current smokers do indeed use e-cigarettes in situations where they cannot smoke cigarettes. [36][37][38] If permitted in smoke-free areas, e-cigarettes could be used to subvert smoking restrictions and re-normalize smoking. 6 Social denormalization of smoking played a critical role in reducing smoking prevalence and youth initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Shiffman, Pillitteri, Burton, and Di Marino (2004) did show that simulated ads describing Eclipse reduced intentions to quit among smokers, and Hughes, Keely, and Callas (2005) showed that Eclipse users were no more or less likely to have quit at 6 months follow-up compared with other smokers. More recently, several studies have evaluated the use of e-cigarettes by cigarette smokers, which indicate that smokers report using them to help quit or cut down on smoking (Adkison et al, 2013;Etter, 2010;Etter & Bullen, 2011;Pearson, Richardson, Niaura, Vallone, & Abrams, 2012;Pokhrel, Fagan, Little, Kawamoto, & Herzog, 2013;Regan, Promoff, Dube, & Arrazola, 2013;Vickerman, Carpenter, Altman, Nash, & Zbikowski, 2013). None of the unconventional tobacco products evaluated in this study have been approved as smoking cessation aids.…”
Section: Introductionmentioning
confidence: 99%
“…The extant literature on consumer perceptions of e-cigarettes is limited and focuses primarily on self-reported reasons for e-cigarette use (Adkison et al, 2013;Dawkins et al, 2013;Farsalinos et al, 2014;Goniewicz et al, 2013;Pepper et al, 2014;Richardson et al, 2014;Vickerman et al, 2013;Zhu et al, 2014), which is only one aspect of consumer perceptions. Based on survey data, frequently endorsed reasons for e-cigarette use include: aiding in conventional cigarette smoking cessation (Dawkins et al, 2013;Farsalinos et al, 2014;Pepper et al, 2014;Zhu et al, 2014); the ability to use e-cigarettes anywhere (Dawkins et al, 2013;Pepper et al, 2014); the limited amount of secondhand "smoke" produced (Farsalinos et al, 2014); and consumer perceptions of less harm than conventional cigarettes (Etter and Bullen, 2011;Pepper et al, 2014;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%